The Effect of Hypnobreastfeeding on Milk Production in Stunting Prevention Efforts in North Tapanuli District - Emilia Silvana Sitompul; Juana Linda Simbolon (Postgraduate, University of Mataram, 2023)
Indonesia is still facing nutrition problems that affect the quality of human resources. The problem of malnutrition is still quite high in Indonesia, especially the problem of stunting. Stunting can occur as a result of malnutrition, especially during 1000 HPK. The Lancet Breastfeeding 2016 states that breastfeeding can reduce infant mortality due to infection by 88%, besides that breastfeeding also contributes to reducing the risk of stunting in the future. Hypnobreastfeeding helps mothers ensure that they can continue to breastfeed, at least exclusively for the first six months. To prevent stunting, optimizing breastfeeding with Hypnobreastfeeding can reduce stunting rates in the North Tapanuli Regency so that the Sustainable Development Goals (SDGs) target in 2025 can be achieved by a 40% reduction. The study aims to determine the difference in prolactin hormone levels before and after the application of hypnobreastfeeding in breastfeeding mothers. The research was a quasi-experiment using pre and Post-tests with a control group design. The sampling technique used purposive sampling on postpartum mothers with a total sample of 30 people. This research was conducted in July-November. Statistical tests using the Wilcoxon test.Â To determine the difference in prolactin levels before and after hypnobreasfeeding, the p-value = 0.02, so that the p-value <0.05 can be concluded that there is a difference in prolactin hormone levels before and after the application of hypnobreastfeeding in nursing mothers. Based on the results of the study, hypnobreastfeeding can be an intervention for breastfeeding mothers to succeed in exclusive breastfeeding.